Edukasi Senam Kaki diabetik untuk meningkatkan Pemahaman dan kemandirian pasien dalam Perawatan Kaki Diabetik secara mandiri - Sari, Putri Irwanti; Sulistiawan, Andika; Sari, Yulia Indah Permata; Martawinarti, Rts Netisa; Poniyem; Poniar, Nanda; Gustina, Ravia; Angela, Fanesa; Mutmainnah, Muthia; Andini, Febri Tri; Oktaria, Rina; Ekaputri, Kintan Resqitha (Jurusan Keperawatan Fakultas Kedokteran dan Ilmu Kesehatan Universitas Jambi, 2025)
Diabetes Mellitus (DM) is a chronic metabolic disorder that triggers various serious complications, including peripheral neuropathy and diabetic foot ulcers. Prevention of these complications is a priority in DM management, one of which is through non-pharmacological interventions such as diabetic foot exercises. This educational activity on diabetic foot exercises at Raden Mattaher Regional General Hospital in Jambi aims to improve the understanding and skills of patients' families in caring for the feet of DM sufferers. Through lectures, discussions, and demonstrations, participants are expected to recognize the benefits of foot exercises, such as improved blood circulation, foot sensitivity, reduced blood glucose levels, and wound prevention. Evaluation of the activity showed that diabetic foot exercises are effective in reducing the risk of foot complications and improving the quality of life of sufferers. This education also emphasized the innovative use of simple tools such as newspaper and the empowerment of health cadres as part of the program's sustainability strategy. Thus, this outreach is a strategic step in strengthening the educational role of health services for families of diabetes patients in hospitals.